The EFFECT OF FOOD AND BEVERAGE SERVICE QUALITY ON CUSTOMER SATISFACTION AT THE GRAND SAVERO BOGOR HOTEL - Lefka Ainayya; Syifa Syaroh Ikhsani (Universitas Pendidikan Ganesha, 2022)
The increasing development of hotels in Indonesia makes competition in the hospitality sector even higher. Every hotel is required to be able to compete in the market and provide quality services or products so that consumers are satisfied with the services or products provided. One of the departement in the hotel that produces a product (Food and Beverage) is food and beverage. Food and Beverage can develop move attractive Food and Beverage products and always make an updated menu to encourage the interest of guests who stay and do not stay and are interested in buying products made by Food and Beverage. This study aims to determine the effect of service quality from Food and Beverage at Hotel Grand Savero Bogor on customer for satisfaction.